Detection and Genotyping of Human Papilloma Virus-Associated Oral Lichen Planus By In Situ Hybridization Technique - Mohammed Ali, Saad H. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Molecular DNA hybridization has confirmed more than 120 different human papilloma virus (HPV) genotypes. A small group of them have high- risk oncogenic potential. Many studies have described an association of such high risk-HPV genotypes with a variety of oral lesions including squamous cell carcinoma, leukoplakia, and lichen planus. Materials and Methods: A total number of 42 tissue specimens, representing 27 patients with oral lichen planus and 15 apparently-healthy oral tissues, were included in this study. The molecular methods for HPV detection and genotyping were performed by in situ hybridization(ISH) using cocktailed- and specific high- risk HPV DNA probes, respectively. Results:The overall percentage of HPV in the total group of patients with oral lichen planus (OLP) was 33.3 %. Negative HPV DNA- ISH reactions were detected in all tissues of the control group. The overall genotyping results revealed HPV 16- DNA in all HPV- positive oral lichen planus tissues , while none of these OLP tissues showed ISH reactions for HPV 18-DNA or HPV 31/33- DNA. Conclusions: The significant incidence of such high oncogenic HPV genotype in those patients with oral precancerous lesions could have a relevant importance along its pathogenesis and the multisteps oral carcinogenesis , HPV-16-associated oral lichen planus that has mostly previliged the site of cheek mucosa represents a herald indicator for spread of such sexually important transmitted infection among Iraqi general population.